Interval Boundary Correction for Interval Linear Program (Contemporary Mathematics, 2025)
An interval linear programming problem is a bounded problem when all of its deterministic problems are bounded. However, if the best deterministic problem is unbounded or the worst deterministic problem is infeasible, a pre-processing step on tightening interval parameter boundaries should be employed to obtain an adjusted bounded interval linear program. With the help of the duality theorem, we propose an interval boundary correction algorithm designed to minimize the loss of interval information. The algorithm makes relatively small adjustments with respect to the interval width of each interval parameter boundary. Some numerical examples illustrating this correction algorithm are provided.
Keywords: interval linear programming; infeasible systems; interval boundary correction; duality theorem